Perubahan Peran Seniman dalam Dinamika Ruang Publik di Taman Ismail Marzuki (1968-2018) - Niken Flora Rinjani (Umbara, 2020)
This paper shows how physical reconstructions and managerial development of the Jakarta Arts Center -Taman Ismail Marzuki (PKJ-TIM), have changed the role of artists at that arts center. TIM which has been established for 50 years is the largest arts center in Jakarta, and eventually became a hub for national and international artistic exchanges. This study uses a conceptual framework relating the locality to supralocal structures, to see TIM as a public space as well as a social space that form the sense of place among the artists. The research method used is ethnography. Data was collected through participant-observation, in-depth interviews, literature reviews, and documentation. The study found that social relationships between artists and their peers inside and outside of TIM, the TIM management, the public at TIM and with the physical environment of TIM, create a sense of place for artists. There are differences in the role of TIM artists in the past (during the reign of DKI Jakarta Governor Ali Sadikin) and at present, following subsequent shifts of DKI Jakarta administration. The place has undergone several restorations. The role of artists in TIM has been slowly reduced from being active actors and managers of art activities at TIM, to only being art performers. The changes have decreased the artists’ interest of TIM as a center for their artistic enterprise. In the artists’ language, TIM has become a place for art activities that lose the spirit of artistry. In conclusion, changes in the artists’ role at the TIM is related to the wider structure, namely the Provincial Government of DKI Jakarta, and their relations with fellow artist and arts institutions at the local, national, and even international level.